KAJIAN INTERAKSI SIMBOLIK POLA KOMUNIKASI ETNIS ARAB DAN ETNIS SUNDA DALAM PERKAWINAN MUT’AH DI KECAMATAN PACET KABUPATEN CIANJUR - Yessi Sri Utami (Jurnal Ilmiah Komunikasi Makna, 2015)
Symbolic Interaction study in this article analyze about pattern of communication Arabic Etnic and Sundanesse Etnic in Mut’ah merriage at Cipanas Cianjur. This study describing four the communication event where two communicative events is dawwir/ دور (looking) and Ittifaq / ات فــاق (agreement) explain the process of human trafficking in mut’ah merriage. Two communicative events is zawaaj /  زواج (marry) and talaq /  ق ا (divorce) showed weak position of women in marriage Mut’ah. Continuous interaction directly or mediated creating the relationships between individuals. Human communication based on the meanings about something to mutual understanding among such individuals. George Herbert Mead’s concept through language that people have the ability to be a subject and an object for himself on the pattern of communication in Mut’ah married with families of both. Generalized other’s concept of the patterns of communication between husband and wife with communities such asrelationship with khadamah, driver / guide, government the MUI and other communities. Nickname such as Jablay / JBL or Onta by society is a fact of implicit interaction in communities around the villa Kota Bunga Cipanas Cianjur. Keywords: intercultural communication, Arabic Ethnic, Sundanesse Etnic, Pattern of Communication, symbolic interaction theory.